Mice are nice - Larrick Nancy; Young Ed (New York : Philomel Books, 1990)
A collection of poems about mice by David McCord, A. A. Milne, John Ciardi, Ian Serraillier, and others.
Includes index.
Keywords: Mice -- Juvenile poetry; Children's poetry; Mice -- Poetry; Poetry -- Collections